Communication: the key for an effective interagency collaboration within the bushfire investigation network. Issue 3 (4th June 2020) - De Sisto, Marco; Handmer, John
Abstract : Purpose: The purpose of this study is to identify strengths and weaknesses in knowledge sharing between related post-bushfire investigative agencies. Based on this study, such a sharing of knowledge is essential to enhance collaboration amongst practitioners in the reduction and management of the risk of bushfires. Design/methodology/approach: The authors use a case study methodology; the research design is based on comparative analysis of six post-bushfire investigative departments in Italy and Australia (Victoria). A total of 44 bushfire investigators were interviewed between 2012 and 2013, across the two countries. Using focus groups and face-to-face interviews, the extent and quality of intra- and interagency knowledge sharing is analysed. Findings: Despite the desire to collaborate, there are three main conditions that prevent an effective interagency collaboration within the bushfire investigation network, namely, separation, unidirectionality and interpersonal disengagement. This study finds that knowledge sharing suffers from a missing "feedback system" culture, where agencies give each other feedback with strictly bureaucratic purposes, rather than create an ongoing learning mechanism that develops after every investigation. At agency level, we also find that, sharing investigative knowledge and experience through daily and planned meetings is a standard practice to police members; but this is not found in the fire agencies. When made cross-country comparisons between Australia and Italy, the existence of common courses, joint manuals and the sharing of human resources witnessed in Australia (Victoria) is something that would benefit Italian agencies still trapped in a competitive and jurisdictional mindset. At the same time, Australian agencies might want to reconsider the separation between bushfire suppression and investigation, a distinction that has been made clear in Italy through the creation of full-time bushfire investigator positions. Practical implications: This paper contributes to the improvement of interagency collaboration through the development of an investigative "social knowledge". It reinforces the assumption that, to reduce and effectively manage the risk of bushfires, a combined effort from different stakeholders involved in forensic investigation is necessary. Originality/value: Given the lack of research undertaken in the area of bushfire investigation, the current paper represents a unique piece of work. It is unusual, not only in identifying the current issues within the bushfire investigation network but also in providing agencies with theoretical and practical insights on how to reduce the extremely high number of bushfires and their risks.